Basic Life Support (BLS) Training in Increasing Knowledge of Helping Cardiac Arrest Patient at Senior High School 1 Puri Mojokerto - kusumawardhany, rini; Dharianta, Rifqy; Santoso , Budi; Nugroho, Dhani Tri Wahyu (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The case of cardiac arrest that caused a young badminton player from China, Zhang Zhi Jie, to die on Sunday 30th April 2024, apparently has also been experienced by a number of world athletes. Sudden cardiac arrest is one of the main causes of death that can be prevented if appropriate treatment is given quickly. In Indonesia, general public knowledge regarding first aid for cardiac arrest, especially among high school students, is still limited. Training uses demonstration methods with posters and LCD monitors. Pre-test and post-test are used to asses knowledge to students of SMAN 1 Puri Mojokerto. The level of knowledge before and after education in the low category decreased from 36.1% to 6%. At the medium level of knowledge (41-70) this decreased from 48.2% to 30.1%. The level of good knowledge has increased from 15.7% to 63.9%.There was an increase in participants' knowledge as shown by the post test scores. It is important to carry out training regarding basic life support for teenagers who are high school level students so that they can carry out RJP actions which are part of providing basic life support properly and correctly.